Unwanted sex : the culture of intimidation and the failure of law - Schulhofer, Stephen J. (Cambridge, Mass. : Harvard University Press, 1998)
With this volume, Stephen J. Schulhofer, Julius Kreeger Professor of Law and Criminology and Director of the Center for Studies in Criminal Justice at the University of Chicago Law School, joins the energetic debate over the legal treatment of sexual assault and abuse. Schulhofer distinguishes his work from that of other scholars by asserting a new entitlement, the right to sexual autonomy: that is, "the freedom of every person to decide whether or when to engage in sexual relations," without coercion or constraint (p. 99). In his construction, sexual autonomy has three components: "an internal capacity to make mature and rational choices ... an external freedom from impermissible pressures and constraints, [and] the bodily integrity of the individual" (p.111). This right to bodily integrity requires that the burden rests on he who seeks consent for sex, not on the other party to demonstrate that she declined. Thus, he maintains, "[e]ven without making threats that restrict the exercise of free choice, an individual violates a woman's autonomy when he engages in sexual conduct without ensuring that he has her valid consent" (p. 111).
Unchecked abuses -- Disappointing reforms -- Fear and desire -- The search for solutions -- Feminist conceptions/judicial innovations -- The missing entitlement: sexual autonomy -- Sexual coercion: the problem of threats and resistance -- Sexual bargaining: legitimate and illegitimate offers -- Supervisors and teachers: the problem of power -- Psychiatrists and psychologists: the problem of trust -- Doctors and lawyers: the problem of professional authority -- Dating: what counts as consent? -- Taking sexual autonomy seriously -- Model criminal statute for sexual offenses.
Includes bibliographical references (pages 285-314) and index.
Keywords: Sex crimes -- United States; Sexual harassment -- Law and legislation -- United States; Sex and law -- United States; Law reform -- United States